The utility of moment ratios and abbreviated endpoints of the multiple breath washout test in preschool children with cystic fibrosis. Issue 3 (3rd January 2020) - Shaw, Michelle; Oppelaar, Martinus C.; Jensen, Renee; Stanojevic, Sanja; Davis, Stephanie D.; Retsch‐Bogart, George; Ratjen, Felix A.
Abstract: Background: The multiple breath washout (MBW) test may be most useful in tracking disease progression over time to inform treatment decisions. In the clinical setting, alternative outcomes, which can be obtained quickly and easily, may facilitate interpretation of clinically relevant changes in lung function. Methods: In this secondary analysis of data from 78 cystic fibrosis (CF) and 72 healthy control (HC) subjects between the ages of 2.6 and 5.9 years, MBW was performed at enrollment, 1, 3, 6, 9, and 12 months, as well as during symptomatic visits using the Exhalyzer D (EcoMedics AG, Duernten, Switzerland). The lung clearance index, LCI2.5, was compared to moment ratios (M1 /M0 and M2 /M0 ) at the standard cutoff (1/40th of starting tracer gas concentration) as well as LCI5 and moment ratios at 1/20th of the starting concentration (M1 /M0 at LCI5, and M2 /M0 at LCI5 ). Results: All outcomes were able to distinguish between health and disease. LCI5 reduced testing time by 40% and increased feasibility by more than 10%. The limits of biological reproducibility in healthy children were similar between LCI2.5 (15%), LCI5 (12%), M1 /M0 at LCI2.5 (14%), and M1 /M0 at LCI5 (12%), but markedly larger for M2 /M0 at LCI2.5 (30%) and M2 /M0 at LCI5 (25%). Each outcome deteriorated significantly with worsening pulmonary symptoms, the magnitude of deterioration was greatest for M2 /M0 . Conclusions: In preschool children with CF, LCI5 was more feasible to obtain and track disease progression. The second moment ratio was most sensitive to pulmonary symptoms, but had the greatest variability both within and between subjects.